Play, Community and Democracy: Understanding How Pay can Stimulate Democracy - Duncan, Samuel Keith (Cosmos and History: The Journal of Natural and Social Philosophy, 2017)
<!--[if gte mso 9]> <![endif]--> This paper explores the link between play, community and democracy to illuminate how play can stimulate vibrant communities which manifest democracy. To expound the link between play, community and democracy, this paper first highlights the notion of democracy and the democratic principles that underpinned Australia's Federation in 1901. Play is then explored to demonstrate how play can stimulate relationships and communities which promulgate the democratic principles on which Australian was founded. Furthermore, this paper highlights the dangers of play's commodification in today's commercial era of sport. If play is corrupted, the formation of communities and the way they operate will also be damaged, thus undermining democracy. <!--[if gte mso 9]> Normal 0 false false false EN-AU X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->